2020
DOI: 10.1002/qua.26482
|View full text |Cite
|
Sign up to set email alerts
|

A systematic benchmarking of 31P and 19F NMR chemical shift predictions using different DFT/GIAO methods and applying linear regression to improve the prediction accuracy

Abstract: A systematic benchmark study of phosphorus and fluorine nuclear magnetic resonance chemical shift predictions using six different density functional theory (DFT)/the gauge‐including atomic orbital (GIAO) methods was conducted. Two databases were compiled: one consists of 35 phosphorus‐containing molecules, which cover the most common intramolecular bonding environments of trivalent and pentavalent phosphorus atoms; the other is composed of 46 fluorine‐containing molecules. The characteristics of each DFT/GIAO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…To make the developed F-GCN better focus on local environment solution, in the readout stage (R-S), a summation of all fragmentary contributions, along with the routine descriptors that are generated by RDKit, 46 will be further conducted by a dense neural network unit (more details can be seen in Figure 2). It is also worth noting that, within our frame, some extra yet related chemical knowledge, like QM calculated descriptors, [19][20][21][22]47 can also be incorporated freely to further augment the performance of F-GCN.…”
Section: Methodsmentioning
confidence: 99%
“…To make the developed F-GCN better focus on local environment solution, in the readout stage (R-S), a summation of all fragmentary contributions, along with the routine descriptors that are generated by RDKit, 46 will be further conducted by a dense neural network unit (more details can be seen in Figure 2). It is also worth noting that, within our frame, some extra yet related chemical knowledge, like QM calculated descriptors, [19][20][21][22]47 can also be incorporated freely to further augment the performance of F-GCN.…”
Section: Methodsmentioning
confidence: 99%
“…some extra yet related chemical knowledge, like QM calculated descriptors, [19][20][21][22]47 can also be incorporated freely to further augment the performance of F-GCN.…”
Section: Methodsmentioning
confidence: 99%
“…[33] The relative 1 H, 13 C, and 31 P chemical shifts (δH, δC, δP) were estimated using the corresponding internal standard (TMS for 1 H and 13 C, H3PO4 for 31 P) shielding calculated at the same level of theory and again using the same implicit solvent model. Scaling of the data was done in accordance with Zhang et al, Benassi, and Lodewyk et al [34,35,36] All energies used and reported in this work are zero-point vibrational-corrected. Visualization was done using Chemcraft software.…”
Section: Computational Chemistrymentioning
confidence: 99%